Comercio, conflicto militar y violencia legal - José Antonio Mateos Royo (Mélanges de la Casa de Velázquez)
Through the policy of the Diputación in Aragon between 1514 and 1559 this article studies the ability of regional representative institutions at the beginning of the early modern age to protect the foreign trade in their territories. The Diputación’s management was properly financed and politically backed by the regional ruling elites as it upheld their economic interests. By combining coherence, regularity and flexibility, its strategy moderated increasing restrictions from the Spanish monarchy regarding trade between Aragon and France. With the cooperation of Béarn’s royal authorities, it wiped out the seizures of goods between Aragonese and Bearnese merchants through the promotion of mediations, restitutions of assets and faster conclusions of legal disputes.